The role of law in decisions to withhold and withdraw life-sustaining treatment from adults who lack capacity: a cross-sectional study. Issue 5 (16th August 2016) - White, Benjamin P; Willmott, Lindy; Williams, Gail; Cartwright, Colleen; Parker, Malcolm
Abstract : Objectives: To determine the role played by law in medical specialists' decision-making about withholding and withdrawing life-sustaining treatment from adults who lack capacity, and the extent to which legal knowledge affects whether law is followed. Design: Cross-sectional postal survey of medical specialists. Setting: The two largest Australian states by population. Participants: 649 medical specialists from seven specialties most likely to be involved in end-of-life decision-making in the acute setting. Main outcome measures: Compliance with law and the impact of legal knowledge on compliance. Results: 649 medical specialists (of 2104 potential participants) completed the survey (response rate 31%). Responses to a hypothetical scenario found a potential low rate of legal compliance, 32% (95% CI 28% to 36%). Knowledge of the law and legal compliance were associated: within compliers, 86% (95% CI 83% to 91%) had specific knowledge of the relevant aspect of the law, compared with 60% (95% CI 55% to 65%) within non-compliers. However, the reasons medical specialists gave for making decisions did not vary according to legal knowledge. Conclusions: Medical specialists prioritise patient-related clinical factors over law when confronted with a scenario where legal compliance is inconsistent with what they believe is clinically indicated. Although legally knowledgeable specialists were more likely to comply with the law, compliance in the scenario was not motivated by an intention to follow law. Ethical considerations (which are different from, but often align with, law) are suggested as a more important influence in clinical decision-making. More education and training of doctors is needed to demonstrate the role, relevance and utility of law in end-of-life care.